2016
DOI: 10.1007/s10107-016-1000-z
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining lower bounds from the progressive hedging algorithm for stochastic mixed-integer programs

Abstract: We present a method for computing lower bounds in the progressive hedging algorithm (PHA) for two-stage and multi-stage stochastic mixed-integer programs. Computing lower bounds in the PHA allows one to assess the quality of the solutions generated by the algorithm contemporaneously. The lower bounds can be computed in any iteration of the algorithm by using dual prices that are calculated during execution of the standard PHA. We report computational results on stochastic unit commitment and stochastic server … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 40 publications
(72 reference statements)
2
128
0
Order By: Relevance
“…However, the allocation of scenarios was random since no criterion concerning which scenarios would be grouped into the same bundle was given. Gade et al incorporated scenario bundling into the PHA for two-stage SMIPs and present a method to compute lower bounds for the purpose of assessing the quality of the solutions generated by the PHA [9]. In their work, all bundles are of the same size and there are no common scenarios between any two bundles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the allocation of scenarios was random since no criterion concerning which scenarios would be grouped into the same bundle was given. Gade et al incorporated scenario bundling into the PHA for two-stage SMIPs and present a method to compute lower bounds for the purpose of assessing the quality of the solutions generated by the PHA [9]. In their work, all bundles are of the same size and there are no common scenarios between any two bundles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of the PHA can be enhanced by replacing the preceding scenario decomposition with bundle decomposition [5,9], where individual scenarios are combined into bundles and the extensive form is decomposed using scenario bundles into multi-scenario subproblems. In contrast to scenario decomposition, the bundle version of the PHA solves smaller numbers of larger subproblems [7].…”
Section: Introductionmentioning
confidence: 99%
“…The basic PH algorithm for two-stage stochastic mixed-integer programs proceeds as follows [8]: While convergence is not guaranteed for mixed-integer problems, computational studies have shown that the PH algorithm can find high-quality solutions within a reasonable number of iterations [25]. The PH algorithm also applies to multi-stage stochastic programs with discrete variables in any stage.…”
Section: Progressive Hedgingmentioning
confidence: 99%
“…We now demonstrate how PH and DD can be integrated through their lower bounds. We first review the lower bounding technique for the PH algorithm proposed by Gade et al [8] and recall equivalence between the best lower bounds obtained by the PH algorithm and the Lagrangian dual from the DD algorithm. Finally, we establish relationships between PH weights and DD multipliers.…”
Section: Integration Of Ph and Ddmentioning
confidence: 99%
See 1 more Smart Citation